Sintesis dan Karakterisasi Titanium Oksida Dalam Cairan Ion 1-Butil-3-Metil Imidazolium Klorida dengan Metode Hidrotermal - Enriyani, Riri; Zulfikar, Muhammad Ali; Alni, Anita (Jurnal Kartika Kimia, 2022)
In this study, TiO2 was synthesized using the hydrothermal method which the solvent used was a mixture of 1-butyl-3-methyl imidazolium chloride ion (BMIM Cl) with water in a ratio of 3:7 v/v. Ionic liquid of 1-butyl-3-methyl imidazole was synthesized with methyl imidazole and chlorobutane as precursors and then characterized using 43 MHz NMR. TiO2 which had been synthesized with BMIM Cl : water (3:7 v/v) was then characterized using XRD, SEM, UV-Vis/DR and BET then compared the results with TiO2 synthesized with water solvent. Based on of XRD analysis was obtained that TiO2 was synthesized by BMIM Cl : water (3:7 v/v) and water solvent produced anatase and brochite crystals where the crystal size of TiO2 synthesized with BMIM Cl : water (3:7 v/v) as solvent was smaller that is 17.70 nm and which is synthesized with water solvent is about 20.35 nm. Based on the SEM characterization data, the morphological structure was more homogeneous. Based on the characterization data using UV-Vis/DR and BET, it was obtained that TiO2 synthesized with BMIM Cl : water (3:7 v/v) had a bigger band gap and larger surface area and pores than TiO2 synthesized by water solvent.